2011
DOI: 10.1021/nl200552r
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Heterojunction Photovoltaic Active Layers via Bilayer Interdiffusion

Abstract: To better understand the physics of the photoactive layer in the organic photovoltaic devices, it is necessary to gain a quantitative understanding of the morphology and the manner in which it develops. A key element in the kinetics associated with the structure development is the interdiffusion of the components. To that end we used P3HT/PCBM bilayers as a model to investigate the interdiffusion of the components and its role in the development of the morphology. A detailed description of the diffusion behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
385
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(426 citation statements)
references
References 48 publications
39
385
2
Order By: Relevance
“…Specifically, more PCBM is accumulated in the surface layer and the mid-layer adjacent to the surface layer in the MD-P3HT/PCBM film. It has been shown that the degree of PCBM diffusion in a P3HT matrix is closely related to the crystallinity of P3HT in that PCBM more easily passes through amorphous P3HT than crystalline P3HT 13 . In the present work, the crystallinity of P3HT and SD-P3HT were found to be comparable while that of MD-P3HT was significantly poorer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, more PCBM is accumulated in the surface layer and the mid-layer adjacent to the surface layer in the MD-P3HT/PCBM film. It has been shown that the degree of PCBM diffusion in a P3HT matrix is closely related to the crystallinity of P3HT in that PCBM more easily passes through amorphous P3HT than crystalline P3HT 13 . In the present work, the crystallinity of P3HT and SD-P3HT were found to be comparable while that of MD-P3HT was significantly poorer.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to an increasing interest in taking advantage of the nanometer scale resolution provided by neutron reflectometry (NR)/scattering to probe the structure, interface and morphology of bulk heterojunctions (BHJ) in organic photovoltaics (OPV) [9][10][11][12][13][14][15] to determine not only the nanoscopic heterogeneity of donor/acceptor components, but their degree of mixing and the vertical composition. The nanoscopic morphological information provided by isotopic substitution is highly relevant to understand exciton diffusion and charge transport in these devices [9][10][11][12][13][14][15] ; however, deuteration is commonly believed to have little effect on morphology. Only recently, small-angle neutron scattering revealed that deuterium substitution can significantly influence the phase separation kinetics and morphology in some polymer blend systems 16,17 .…”
mentioning
confidence: 99%
“…With TEM and GIXD experiments, they confirmed that the diffusion process did not disrupt the morphology established by P3HT and the interdiffusion driven morphology is essentially the same with homogenously mixed BHJ active layer. 56 In fact, the device performances achieved with this postdiffusion route were as good as when the P3HT and PCBM were initially uniformly mixed. [56][57][58][59] Solvent Annealing Approach Solvent annealing is another effective method that has been used to induce phase separation in P3HT:PCBM blends.…”
Section: Thermal Annealing Approachmentioning
confidence: 92%
“…56 In fact, the device performances achieved with this postdiffusion route were as good as when the P3HT and PCBM were initially uniformly mixed. [56][57][58][59] Solvent Annealing Approach Solvent annealing is another effective method that has been used to induce phase separation in P3HT:PCBM blends. When the solvent vapor enters the mixture, the mobility of both the P3HTand PCBM increases, enabling the P3HT to crystallize and drive the segregation of the PCBM.…”
Section: Thermal Annealing Approachmentioning
confidence: 92%
“…However, this may not be as stable as a fully conjugated donor-acceptor block copolymer system due to the migration and movement of PCBM through the polymer film. For example, recent work has shown that the complete diffusion of PCBM through amorphous P3HT (100-nm thick film) takes place within $5 s at 150 C. 217 The work of Gu et al 218 provides an example of a block copolymer and PCBM system. Here, they synthesized a P3HT-block-PS copolymer and added PCBM to make devices that had a maximum optimized device efficiency of 1.93% after thermally annealing the layer.…”
Section: Processingmentioning
confidence: 99%